What Shapes Taiwan-related Legislation in U.S. Congress?. Issue 136 (4th July 2022) - Lin, Gang; Zhou, Wenxing; Wu, Weixu
ABSTRACT: Through a quantitative analysis of Taiwan–related legislation between 1979 and 2020, the article finds that the degree of Taiwan–related legislation is significantly correlated with the degree of tension in U.S.—China relations. While a deteriorating cross–Taiwan Strait relationship is clearly associated with the increasing legislative activities for the sake of Taiwan, an improving relationship from the state of fair to good cannot guarantee a decrease of such activities. A unified government and the extent of the Taiwan lobby are both helpful in passing pro–Taiwan acts but statistically insignificant. A content analysis of pro–Taiwan bills approved by the Trump administration suggests a creeping movement to "normalize" U.S–Taiwan relations with congressional activism and the less-restrained White House as a co–engine.